EFFECT OF WORK FACILITIES AND SALARIES ON EMPLOYEE PRODUCTIVITY THE BRASTAGI SUPERMARKET MEDAN - LG, Lambas Marasi Tua; Mulia Sirait, Ronnie Togar (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The purpose of the study was to determine partially or simultaneously the effect of salary and work facilities on the productivity of teachers at Al Washliyah 20 Medan private junior high school. This study descriptive quan1titative questionnaire instrument. The study population amounted to 35 teachers with saturated sample technique then the sample of 35 people. The results of the study were the value of tcount work facilities 2.303, value ttable 2.032; value tcount > ttable and sigcount < sigtable (2.303 > 2.032) and (0.000 < 0.05). Value tcount salary 5.777, value ttable 2.032; value tcount > ttable and sigcount < sigtable (5.777 > 2.032) and (0.000 < 0.05). Value Fcount facilities and salaries 16.756, value Ftable 2.882; value Fcount > Ftable and sighcount < sigtable (16.756 > 2.882) and (0.000 < 0.05). Rsquare value is 0.712 or R2 x 100% of 71.20%, meaning that the independent variable contributes greatly to describe the productivity of teachers at 71.20% the remaining 28.0% influenced by other factors.